Acetazolamide for Partial Seizures - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1989)
Acetazolamide (Diamox) (AZM) was tried as an adjunct to carbamazepine (CBZ) in 48 refractory partial seizure patients, the majority being adults and only 5 under 12 years of age.